The Role of the Turjawali Sat Samapta Two-Wheel Patrol Unit in Preventing the Crime of Theft by Weighting in the Jurisdiction of the Ngawi Police (Indonesian Journal of Police Studies, 2024)
This research is motivated by the increasing incidence of aggravated theft (Currat) in the jurisdiction area of Polres Ngawi from 2020 to 2023. The occurrence of Currat crimes in the Polres Ngawi jurisdiction area undoubtedly creates concerns, discomfort, and fear in society, increases mental and physical well-being issues for victims, directly harms victims, provides opportunities for youth involvement in criminal activities which subsequently disrupts their education and potential development, and raises concerns about road safety, especially in vulnerable areas and at certain times such as nighttime. The aim of this study is to provide an overview of aggravated theft in the jurisdiction area of Polres Ngawi, through a general description of the crime as well as the roles and factors influencing the implementation of the two-wheeled patrol Unit Turjawali Samapta Patrol in preventing it, with the ultimate goal of enhancing the effectiveness of crime prevention and control efforts in the area. The theories and concepts used include role concept, two-wheeled patrol concept, Unit Turjawali Samapta concept, aggravated theft concept, routine activity theory, and management theory. The method used in this research is qualitative. The results show that aggravated theft in the jurisdiction area of Polres Ngawi is a significant problem with fluctuating numbers of cases. Contributing factors include a lack of witnesses, insufficient CCTV recordings, and difficult economic conditions. The two-wheeled patrols of Unit Turjawali Samapta have played a role in preventing these crimes, although there are still challenges in the management of planning functions, such as identifying vulnerable areas and mapping crime patterns. Factors affecting patrol implementation include human resources availability, Two-Wheeled Patrol SOP, but are hindered by budget constraints, infrastructure limitations, and minimal community support. Therefore, improvements in patrol planning management and increased support and procurement of infrastructure are needed to enhance the effectiveness of crime prevention in the area.
Keywords: Patroli Roda Dua, Currat, Pencurian dengan pemberatan, Pencegahan.